2016
DOI: 10.1371/journal.pone.0109913
|View full text |Cite
|
Sign up to set email alerts
|

Number of Days Required to Estimate Habitual Activity Using Wrist-Worn GENEActiv Accelerometer: A Cross-Sectional Study

Abstract: IntroductionObjective methods like accelerometers are feasible for large studies and may quantify variability in day-to-day physical activity better than self-report. The variability between days suggests that day of the week cannot be ignored in the design and analysis of physical activity studies. The purpose of this paper is to investigate the optimal number of days needed to obtain reliable estimates of weekly habitual physical activity using the wrist-worn GENEActiv accelerometer.MethodsData are from a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 22 publications
2
107
2
Order By: Relevance
“…Wrist‐worn accelerometers have previously been recommended as the best location for accelerometers for wheelchair users, as well as removing any issues of access and comfort that would be associated with other locations (such as mid‐thigh or waist). Monitors were worn for 24 h a day on the preferred wrist of participants and worn continuously for 7 days . Monitors were initialized to collect data at 100 Hz and acceleration values, recorded in g, and recorded continuously on each axis (x, y, and z).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wrist‐worn accelerometers have previously been recommended as the best location for accelerometers for wheelchair users, as well as removing any issues of access and comfort that would be associated with other locations (such as mid‐thigh or waist). Monitors were worn for 24 h a day on the preferred wrist of participants and worn continuously for 7 days . Monitors were initialized to collect data at 100 Hz and acceleration values, recorded in g, and recorded continuously on each axis (x, y, and z).…”
Section: Methodsmentioning
confidence: 99%
“…Monitors were worn for 24 h a day on the preferred wrist of participants and worn continuously for 7 days. 60 Monitors were initialized to collect data at 100 Hz and acceleration values, recorded in g, and recorded continuously on each axis (x, y, and z). Recorded total activity time has been previously validated against doubly labelled water.…”
Section: Physical Activitymentioning
confidence: 99%
“…As with children and younger adults,[25] older adults are less active on weekends, especially on Sundays. For older adults, accelerometry measures of sedentary behavior (%) and light-lifestyle activity (%) are significantly different on both Saturdays and Sundays compared to weekdays.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been carried out in children [9], young [10,11] and adult population [12,13] focused on the numbers of monitoring days necessary to represent habitual PA behavior. Results of these studies suggested a large variability in the number of days required to obtain reliable measures of PA ranging from 2 to 9 days.…”
Section: Introductionmentioning
confidence: 99%
“…Results of these studies suggested a large variability in the number of days required to obtain reliable measures of PA ranging from 2 to 9 days. Also, the number of required days varies according to the intensity of physical activities, often grouped as sedentary behavior, and light, moderate, and vigorous intensity [12,13]. Other factors that can influence the monitoring time-frame are the type of accelerometer used and placement of the device (e.g., wrist, thigh, or waist) [68].…”
Section: Introductionmentioning
confidence: 99%